Diversidade, distribuição e diversificação do gênero Brachycephalus Fitzinger, 1826 (Anura: Brachycephalidae) - Condez, Thais Helena [UNESP] (2014)
The genus Brachycephalus is endemic to the Atlantic forest of Brazil and currently comprises 21 species. Most of them are restricted to high elevation areas along the main mountain ranges of the biome. These species exhibit extremely small adult body size and share morphological features due to evolutionary process of miniaturization. Despite of the recent description of new species, some characteristics, such as diversity, species distribution, and evolutionary history, are still poor understood. Here, we addressed the variation of morphological, ecological, and genetic traits of Brachycephalus populations along their distribution. In the first chapter we described morphometric variation within more than one thousand individuals from several populations and species across the genus distribution. We identified two main groups of species based on body size and snout width variation. These groups are congruent with localities variation in altitude and topographic complexity. We evidenced a relationship between latitude and body size in species associated to high elevation. Higher temperatures were correlated with larger body sizes. Within the flea-toads, the altitudinal widespread species, we found little morphometric variation. In the second chapter we evaluated the current taxonomic hypotheses, mapped and reconstructed the ancestral states for body color, body size, advertisement call, and altitudinal and geographic distributions. Our data confirmed that the genus is monophyletic and we found no molecular evidence of distinction between flea-toads (the formerly called Psyllophryne) and other Brachycephalus species. The analyzed traits were variable across the main clades and our data suggested that the extant species evolved from a dull colored ancestor, without hyperossification in skull and postcranial skeleton, with wide altitudinal range, and short advertisement call composed by one to four high frequency notes with 1-3 pulses. In the...